Acceptance towards sustainable agriculture among contract farmers and its impingement factors - Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Abu Samah, Bahaman; Man, Norsida; Uli, Jegak; Azman, Azmariana (Science Publications, 2012)
Problem statement: Rising demands and needs for food nowadays have put a great pressure on our natural resources. Overuse of the environmental sources has been proven to have profound impact on both; the community and the environment. To solve such problem, sustainable agriculture has been suggested as one of the solutions. Undoubtedly, sustainable agriculture will supply adequate nutrition sources at the present and in the future to the community. In line with this, a lot of efforts have been put to embolden farmers to practise sustainable agriculture. Nonetheless, are the farmers accepting it in their farming routines? The answer of this query will fulfil the main objective of this study which is to discover the level of acceptance of contract farmers in Malaysia on sustainable agriculture. Additionally, socio-demographic factors that impinge the level of acceptance have become another objective for this study. Approach: This is a quantitative study where through a multi stage simple random sampling, a total of 326 contract farmers from four states in Malaysia were chosen as the respondents. Results: Analysis carried out has identified that contract farmers in Malaysia do have a high level of acceptance on sustainable agriculture. Apart from this, factors such as zone and races were identified to have significant difference with acceptance towards sustainable agriculture. Additionally, age was identified to have significant relationship with acceptance towards sustainable agriculture. Conclusion/Recommendation: Several discussions and recommendations have been highlighted and expectantly it can help the concerned parties to further strengthen contract farmers' acceptance towards sustainable agriculture.